The language of hookups a conversation and self-presentation analysis of Tinder chats - Jalagat, Joseph Ryann J. (Plaridel, 2021)
Access online through this link: https://www.plarideljournal.org/article/the-language-of-hookups-a-conversation-and-self-presentation-analysis-of-tinder-chats